1976
DOI: 10.1002/pssb.2220770211
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin‐lattice relaxation of Cu2+ ions in planar coordination geometries: Calculation and experimental data of T1 for Cu2+ in Ni(II) bis(diethyl‐dithiocarbamate) crystals

Abstract: A general formula is derived for the direct spin-lattice relaxation process of paramagnetic ions with 8 = +for arbitrary orientations of an external magnetic field relative to the crystal axes. Using the formula obtained, Tl of Cuzt ions in square planar coordination geometries is calculated in the point charge approximation. The temperature, concentration, and angular dependence of TI of Cu2+ ions in Ni(II)bis(diethyl-dithiocarbamate) single crystals are reported. Including some features of covalency a reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…29 The Orbach-type exp(-E/kT) relaxation was observed for Cu 2+ in Zn(BrO 3 ) 2 ‚6H 2 O, 36 although the T 1 -1 ∝ T 3 dependence was reported for this crystal also. 37 In the all of the above crystals and for Cu 2+ in (NH 4 ) 2 Mg(SO 4 ) 2 ‚6H 2 O the T 1 values in the temperature range 4.2-10 K are of the order of T 1 ) 10 -4 s. This is shorter but not significantly than T 1 for Cu 2+ in crystals without Jahn-Teller effect, e.g., T 1 ) 3 × 10 -4 s for Cu 2+ in triglycine selenate at 10 K, 41 T 1 ) 1 × 10 -2 s for Cu 2+ in Ni bis(diethyldithiocarbamate) at 10 K, 42 and T 1 ) 5 × 10 -2 s for Cu 2+ in LiNbO 3 at 10 K. 43 To have a direct proof that Jahn-Teller dynamics governs the spin relaxation in our crystal, we have measured T 1 for Mn 2+ ions in (NH 4 ) 2 Mg(SO 4 ) 2 ‚6H 2 O along the z-axis direction of the Cu 2+ complex, and we found that at 10 K the T 1 (Mn 2+ ) ) 1 × 10 -2 s. 44 The Mn 2+ is not a Jahn-Teller ion, and its relaxation in the same host lattice is of about 2 orders of magnitude slower than Cu 2+ , indicating a dominat role of the Jahn-Teller dynamics in electron spin relaxation.…”
Section: Electron Spin-lattice Relaxationmentioning
confidence: 83%
“…29 The Orbach-type exp(-E/kT) relaxation was observed for Cu 2+ in Zn(BrO 3 ) 2 ‚6H 2 O, 36 although the T 1 -1 ∝ T 3 dependence was reported for this crystal also. 37 In the all of the above crystals and for Cu 2+ in (NH 4 ) 2 Mg(SO 4 ) 2 ‚6H 2 O the T 1 values in the temperature range 4.2-10 K are of the order of T 1 ) 10 -4 s. This is shorter but not significantly than T 1 for Cu 2+ in crystals without Jahn-Teller effect, e.g., T 1 ) 3 × 10 -4 s for Cu 2+ in triglycine selenate at 10 K, 41 T 1 ) 1 × 10 -2 s for Cu 2+ in Ni bis(diethyldithiocarbamate) at 10 K, 42 and T 1 ) 5 × 10 -2 s for Cu 2+ in LiNbO 3 at 10 K. 43 To have a direct proof that Jahn-Teller dynamics governs the spin relaxation in our crystal, we have measured T 1 for Mn 2+ ions in (NH 4 ) 2 Mg(SO 4 ) 2 ‚6H 2 O along the z-axis direction of the Cu 2+ complex, and we found that at 10 K the T 1 (Mn 2+ ) ) 1 × 10 -2 s. 44 The Mn 2+ is not a Jahn-Teller ion, and its relaxation in the same host lattice is of about 2 orders of magnitude slower than Cu 2+ , indicating a dominat role of the Jahn-Teller dynamics in electron spin relaxation.…”
Section: Electron Spin-lattice Relaxationmentioning
confidence: 83%
“…[12], Ni(diethyldithiocarbamate) 2 (Op = 80 K) [13], LiNbO 3 (Op = 250 K) [7], and triglycine selenate (TGSe) (OD = 168 K) [6]. The Debye temperatures were determined from the relaxation data with the best fit presented by solid lines.…”
Section: Relaxation Rate 1/t and Phonon Spectrummentioning
confidence: 99%
“…The structure and single crystal ESR spectra of Cu(imidazole)4(N03)2 have been described (179). Spin-lattice relaxation for Cu(II) in nickel®) diethyldithiocarbamate has been treated theoretically and experimentally with reasonable agreement between the two (180). Single crystal ESR studies of six-coordinate bis(o)-nitrophenonato)bis(4-methylpyridine)copper(II) in the corresponding zinc(II) chelate have been reported (181).…”
Section: Paramagnetic Inorganic Materialsmentioning
confidence: 99%